Elementos de regulação e microRNAs envolvidos na modulação dos níveis de hemoglobina fetal em indivíduos portadores de beta-hemoglobinopatias - Carrocini, Gisele Cristine de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
High levels of Hb F in adulthood may have beneficial effects for sickle cell anemia and beta-thalassemia. Some of the genetic elements that act in the regulation of Hb F expression are transcription factors and microRNAs. The aim of this study was to use phylogenetic footprinting to screen transcription factors that have binding sites in the γ-globin genes' noncoding regions, and miRNAs candidates to modulating Hb F levels, also evaluating the expression of microRNAs selected from in silico analyses in different groups with distinct profiles of Hb F expression. In silico analysis to screening of transcription factors were performed using bioinformatics tool VISTA, comparing the sequences of HBG1 and HBG2 genes in species of the Old and New World primates with the Homo sapiens sequences. The screening of predicted microRNAs to regulation of γ-globin genes was performed using public databases of microRNA. For the expression analyses of the selected microRNAs, we analized thirty-eight peripheral blood samples, divided into five groups: control group, sickle cell anemia using or not hydroxyurea (HU), and beta-thalassemia with and without allele β0. All samples were tested to hemoglobinopathies by classical diagnostic tests, quantification of globin fractions by chromatography and molecular analyses for genotyping of sickle cell anemia (PCR-RFLP) and beta-thalassemia (PCR-AE and genomic sequencing), and the characterization of haplotypes βS and β-Tal (PCR-RFLP). The reticulocytes were isolated from whole blood and submitted to microRNAs extraction. The analyses of the microRNAs expression were performed by real-time PCR (RT-PCR and qPCR). In silico analyses showed 13 transcription factors conserved between the analyzed species, which have binding sites in non-coding regions of both γ-globin genes, involved in regulating of the Hb F expression: BP1, CDC5, c-MYB, COUPTFII, CP2, GATA-1, GATA-2, NF-E2...

Níveis elevados de Hb F na vida adulta podem apresentar efeitos benéficos para indivíduos com anemia falciforme e talassemia beta. Dentre os elementos genéticos que atuam na regulação da expressão da Hb F são conhecidos os fatores de transcrição e os microRNAs. Os objetivos do trabalho foram rastrear, por footprinting filogenético, fatores de transcrição que apresentam sítios de ligação nas regiões não-codificantes dos genes da γ-globina, e microRNAs candidatos à regulação desses genes, além de avaliar a expressão desses microRNAs selecionados in silico em diferentes grupos de indivíduos com perfis distintos de expressão de Hb F. As análises in silico para o rastreamento dos fatores de transcrição foram realizadas comparando as sequências dos genes HBG1 e HBG2 de espécies de primatas do Velho e do Novo Mundo com as sequências da espécie Homo sapiens. O rastreamento in silico dos microRNAs preditos à regulação dos genes da γ-globina foi realizado a partir da utilização de bancos de dados públicos de microRNA. Para as análises de expressão dos microRNAs selecionados foram analisadas 38 amostras de sangue periférico, divididas em cinco grupos de estudo: grupo controle, anemia falciforme em uso ou não de hidroxiureia (HU), e talassemia beta na presença e ausência do alelo β0. Todas as amostras foram submetidas aos testes clássicos de diagnóstico de hemoglobinopatias, quantificação das frações de globinas por cromatografia e análise molecular para a genotipagem dos indivíduos com anemia falciforme (PCR-RFLP) e talassemia beta (PCR-AE e sequenciamento genômico), além da caracterização dos haplótipos βS e β-Tal (PCR-RFLP). Os reticulócitos foram isolados a partir do sangue total e submetidos à extração de microRNA. As análises de expressão dos microRNAs foram realizadas por PCR em tempo real (RT-PCR e q-PCR). As análises in silico apontaram...
Keywords: Genetica humana; Hemoglobina fetal; Anemia falciforme - Aspectos genéticos; Talassemia beta; MicroRNAs